Imaging Maxillofacial Trauma: The Role of Multidetector Computed Tomography - K.S. Vedaraju; Neha Khatoon P; Sindhura, Pulagam (Asian Journal of Medical Radiological Research, 2022)
Background: Facial fractures account for substantial emergency department visits in the world and are allied with great levels of morbidity and mortality. The maxillofacial region is one amongst the most complex anatomical regions of the human body and is further linked with several crucial daily activities. The main objective of this study was to assess the role of Multislice Computed Tomography in the evaluation of maxillofacial trauma. Subjects and Methods: This Hospital-based prospective study was carried out over 9 months from JAN 2021 to SEP 2021 at the Department of Radiodiagnosis, Narayana medical college, Nellore. The study population included 48 patients- imaged with non-contrast axial 16 slice or 128 slice helical series. In conjunction with the axial images, coronal-plane MPR images were scrutinized to ascertain the presence of facial fractures. 3-Dimensional volume-rendering images were also procured. The GE workstation was used to review MDCT scans. Results: Out of the 48 cases, eight individuals were excluded from our study owing to motion artefacts. The peer age-group of this study was within 30 to 40 years with male preponderance of 70%. RTA was most prevalent mode of injury comprising 67.5% of cases. The maxillary fractures were most frequently eyed in 75% of patients and naso-orbito-ethmoid region accounted for 70% of patients forming the next routinely affected region. Most familiar coexistent finding in the patients with facial injury was hemosinus and spotted in 80% (n=32) patients. Some of the fractures were missed on three-dimensional imaging (3 D) compared to the axial scans but the extent of the complex fracture lines as well as degree of displacement were assessed with increased accuracy. Conclusion: The technological advances in medical imaging, particularly computer software algorithms in CT have fabricated the generation of coronal and sagittal reconstructed images along with 3- Dimensional images expeditious and economical without auxiliary burden of radiation exposure. We conclude that MDCT is highly diagnostic and is, therefore, the best imaging modality for evaluating maxillofacial injuries and its associated findings in backdrop of trauma and thus playing a crucial role in the planning of surgery.